Exploring stress urinary incontinence outcomes after sling excision for perforation or exposure. Issue 4 (22nd March 2019) - Syan, Raveen; Peyronnet, Benoit; Drain, Alice; Enemchukwu, Ekene; Malacarne, Dominique R.; Rosenblum, Nirit; Nitti, Victor W.; Brucker, Benjamin M.
Abstract : Objective: This study assessed stress urinary incontinence (SUI) outcomes after sling excision for urinary tract perforation or vaginal exposure, and compared the outcomes of concomitant versus staged autologous fascia pubovaginal sling (AFPVS). Methods: A retrospective chart review of all patients who underwent midurethral sling (MUS) excision for urinary tract perforation or vaginal exposure at a tertiary referral center between 2010 and 2015 was performed. Therapeutic strategies were categorized as concomitant AFPVS, staged AFPVS, and no anti‐incontinence procedure. Results: In all, 32 patients were included for analysis: 13 with vaginal tape exposure (40.6%) and 19 with urinary tract tape exposure (59.4%). In patients who had SUI prior to sling excision (43.8%), the rate of resolved or improved SUI postoperatively was higher in the concomitant AFPVS group than in those who underwent sling excision alone (83.3% vs 12.5%, respectively; P  = 0.03). Of 18 patients with no SUI prior to sling excision, 12 experienced recurrent SUI after sling removal (66.7%). The rate of recurrent SUI was lower in patients with vaginal MUS exposure than urinary tract MUS perforation, but this did not reach statistical significance (57.1% vs 72.7%, respectively; P  = 0.63). The rates of resolved SUI after AFPVS were comparable in patients with concomitant and staged AFPVS (66.7% vs 71.4%, respectively; P  = 0.99). Conclusions: Many patients with MUS perforations or exposures will have SUI at initial presentation or develop SUI after removal of the synthetic sling. The decision to perform a concomitant AFPVS or to stage the surgical management of SUI can be individualized.